HFE gene mutation is a risk factor for tissue iron accumulation in hemodialysis patients. Issue 3 (23rd January 2017) - Turkmen, Ercan; Yildirim, Tolga; Yilmaz, Rahmi; Hazirolan, Tuncay; Eldem, Gonca; Yilmaz, Engin; Aybal Kutlugun, Aysun; Altindal, Mahmut; Altun, Bulent
Abstract: Introduction: HFE gene mutations are responsible from iron overload in general population. Studies in hemodialysis patients investigated the effect of presence of HFE gene mutations on serum ferritin and transferrin saturation (TSAT) with conflicting results. However effect of HFE mutations on iron overload in hemodialysis patients was not previously extensively studied. Methods: 36 hemodialysis patients (age 51.3 ± 15.6, (18/18) male/female) and 44 healthy control subjects included in this cross sectional study. Hemoglobin, ferritin, TSAT in the preceding 2 years were recorded. Iron and erythropoietin (EPO) administered during this period were calculated. Iron accumulation in heart and liver was detected by MRI. Relationship between HFE gene mutation, hemoglobin, iron parameters and EPO doses, and tissue iron accumulation were determined. Findings: Iron overload was detected in nine (25%) patients. Hemoglobin, iron parameters, weekly EPO doses, and monthly iron doses of patients with and without iron overload were similar. There was no difference between control group and hemodialysis patients with respect to the prevalence of HFE gene mutations. Iron overload was detected in five of eight patients who had HFE gene mutations, but iron overload was present in 4 of 28 patients who had no mutations (P = 0.01). Hemoglobin, iron parameters, erythropoietin, and iron doses were similar in patients with and without gene mutations. HFE gene mutations remained the main determinant of iron overload after multivariate logistic regression analysis (P = 0.02; OR, 11.6). Discussion: Serum iron parameters were not adequate to detect iron overload and HFE gene mutation was found to be an important risk factor for iron accumulation.